Sosialisasi dan Pendampingan Anti Narkoba Karang Taruna di Dusun Clebung Bawah, Soronalan, Sawangan, Magelang - Sukmarani, Dhuta; Deviana Kusma Putri; Fahri Syaiful Anam; Muhammad Bintang Pradana; Ajie Sahara Putra; Muhammad Andika Putra Ramanda (Nusantara Mengabdi Kepada Negeri, 2024)
Clebung Bawah Hamlet is one of the developing areas, there are community organizations such as PKK RT, women's farmer group (KWT), posyandu cadres, youth organization (Karang Taruna), and TPQ children's association. However, there is one educational activity that has not been held in this hamlet, namely outreach about the dangers of drugs, and juvenile delinquency. Apart from that, it is also necessary to reactivate positive community activities, such as village cleaning. To overcome this problem, the methods used through PPMT activities are education through outreach about the dangers of drugs and juvenile delinquency, revitalization of the village cleaning, and greening. The result of PPMT activities is that before the activity, PPMT implementers approach residents by participating in routine community activities such as community service and reciting the Koran. The next activity is to conduct outreach with anti-drug and juvenile delinquency material from a health and legal perspective. The implementation of socialization went smoothly and well. The youth receive material from “Program Pengabdian Masyarakat Terpadu (PPMT)” implementers well. Socialization is one form of activity that can be carried out to educate residents about the dangers of drugs and juvenile delinquency. The next activity is the revitalization of village cleaning activities, which are carried out alongside reforestation and the provision of rubbish bins. Village cleaning and greening activities are positive activities that can be used as alternative activities for teenagers while preserving noble culture and protecting the environment.